The relationship between urinary selenium levels and risk of gestational diabetes mellitus: A nested case–control study - Liu, Yuanxia; Chen, Hongmei; Zhang, Mengtian; Zhu, Gangjiao; Yang, Yan; Li, Yuanyuan; Lu, Wei; Zhang, Hongling (Frontiers in Public Health, 2023)
Background: Selenium (Se) is an essential trace element for the human body. Serum Se and urinary Se are also biomarkers to assess Se exposure status. However, studies focusing on the association between urinary Se and the risk of gestational diabetes mellitus (GDM) are rare. Objective: To investigate the association between urinary Se and the risk of GDM. Methods: A nested case-control study based on a prospective birth cohort in Wuhan, China, which focuses on the effects of prenatal environmental factors exposure on pregnant women and children’s health was conducted. 226 and 452 controls were included. Maternal urine samples were collected before GDM diagnosis, and the urinary Se levels were determined. We assessed the association of urinary Se with GDM by conditional logistic regression with maternal urinary Se level as a categorical variable, and estimated the association between Se and glucose levels by multiple linear regression. The potential modifier roles of maternal age and fetal sex have also been assessed. Results: Lower urinary level of Se was significantly associated with a higher risk of GDM (OR = 2.35 for the tertile 1, 95% CI:1.36, 4.06; adjusted OR = 1.79 for the tertile 2, 95%CI:1.09, 2.95; P for trend = 0.01). Fetal sex had an interaction with Se in the association with GDM. The association was more pronounced among pregnant women with female fetuses than with male fetuses. Discussion: Our study suggested a significant negative association between urinary Se and the risk of GDM, and this association may vary depending on the fetal sex.